INVESTIGATION OF CAVITATION-EROSIVE RESISTANCE OF CAST IRON WITH DIFFERENT FORMS OF GRAPHITE - A. A. Suslov; I. A. Pugachev (Литьë и металлургия)
The technique is developed and researches of cavitational and erosive resistance of cast iron with a various form of graphite – flaked, vermicular and nodular are conducted